2020
DOI: 10.53399/knj.v2i2.46
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Bermain Teraupetik Puzzle Terhadap Tingkat Kecemasan Anak Usia Pra Sekolah di Ruang Anak Rs Bhayangkara Anton Soedjarwo Pontianak

Abstract: Perawatan anak sakit selama di rawat di rumah sakit menimbulkan krisis  dan kecemasan tersendiri bagi anak dan keluarganya. Penelitian ini bertujuan untuk mengetahui pengaruh bermain terapeutik (puzzle) terhadap kecemasan anak usia pra sekolah. Desain penelitian quasi eksperimental pre test and post test without control group dengan besae sampel 30 responden. Hasil penelitian menunjukkan terdapat perbedaan yang bermakna kecemasan anak usia pra sekolah sebelum dan sesudah diberikan bermain terapeutik puzzle (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The teachers of preschool need to apply some ways to teach children's intellectual development as suggested by some previous studies (Afrida et al, 2020;Dwi Nada Fadillah & Wiwin A, 2021;Ismail et al, 2021;Puteh & Salam, n.d.;Rachmi et al, 2021) and also need to understand the psychological factors and the characteristics of preschool children (Fatul & Alias, 2020;Hanur & Rakhmawati, 2021;Sukmawati, 2023;Yuliani et al, 2022;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The teachers of preschool need to apply some ways to teach children's intellectual development as suggested by some previous studies (Afrida et al, 2020;Dwi Nada Fadillah & Wiwin A, 2021;Ismail et al, 2021;Puteh & Salam, n.d.;Rachmi et al, 2021) and also need to understand the psychological factors and the characteristics of preschool children (Fatul & Alias, 2020;Hanur & Rakhmawati, 2021;Sukmawati, 2023;Yuliani et al, 2022;.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on the need to consider children's intellectual development have been done by some researchers (Fatul & Alias, 2020;Hanur & Rakhmawati, 2021;Sukmawati, 2023;Yuliani et al, 2022;. Some other researchers were focusing on a certain way to teach children's intellectual development (Afrida et al, 2020;Dwi Nada Fadillah & Wiwin A, 2021;Ismail et al, 2021;Puteh & Salam, n.d.;Rachmi et al, 2021). The other researchers found that games (Solievna, 2022;Zourmpakis et al, 2022) and technologies (Altboeva, 2021;Anisimova, 2020;Barenthien et al, 2020;Hasanov & Mamataov, 2022) become the keys to success in teaching preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Children who have good health will have optimal growth and children's health standards (Iltiqoiyah, 2020), which include a physical and psychological change in general and have developed according to their age (Kamelia, 2019;Ariyanti, 2016). Pujianto (2019) and Afrida et al,. (2020) Said that children during the exploration period had the characteristics of good health, seemed cheerful, enthusiastic about playing, shouted, ran, jumped, and usually did not want to stay still.…”
Section: Introductionmentioning
confidence: 93%